PENGARUH PENGEMBANGAN KARIR DAN KOMPETENSI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA PT. PERKEBUNAN NUSANTARA XI MEDIKA (PERSERO) RS. ELIZABETH SITUBONDO - Dermawan, Arifandi; Kusnadi, Edy; Ediyanto, Ediyanto (Fakultas Ekonomi dan Bisnis, 2022)
The purpose of the study was to determine the effect of career development and competence on employee performance with work motivation as an intervening variable at PT. Perkebunan Nusantara XI Medika (Persero) RS. Elizabeth Situbondo. The sampling technique used in this study is a saturated sample. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that career development has a positive and significant effect on work motivation, competence has a positive and significant effect on work motivation, career development has a positive and significant effect on employee performance, competence has a positive but not significant effect on performance employees, work motivation has a positive and significant effect on employee performance, career development has a positive and significant effect on employee performance through work motivation, competence has a positive and significant effect on employee performance through work motivation